Análise da estabilidade, variabilidade e complexidade do ligamento cruzado anterior após reconstrução do ligamento cruzado anterior - Oliveira, Eduardo Afonso de (2016)
Background: The objective of this study was to investigate gait stability by nonlinear dynamic methods and gait variability and complexity in the postoperative period after anterior cruciate ligament (ACL) reconstruction. Methods: The study was observational and case-controlled and used 40 subjects (32 male) divided into 4 groups of 20 each: a control group (CG) and 3 observational groups in different postoperative periods after ACL reconstruction: OG-I (30‒90 days), OG-II (90‒180 days), and OG-III (360 days). For kinematic recording, each subject walked on a treadmill for 4 minutes at a constant speed of 3.5 km/h. Gait variability was assessed using the normalized root mean square (RMS ratio) of trunk acceleration and the average standard deviation of medial-lateral trunk acceleration (VAR ML). Gait stability was assessed using the margin of stability (MoS) and local dynamic stability (s), and complexity was assessed using approximate entropy (ApEn). Results: Compared to the CG, the RMS ratio and VAR ML increased significantly in the OG-I group and decreased incrementally in OG-II and OG-III. MoS decreased significantly in the OG-I group and increased incrementally in OG-II and OG-III, while s decreased in the OG-I and OG-II groups and increased in the OG-III groups. The ApEn was lower in the OG-I group than in the CG and decreased incrementally in OG-II and OG-III. Conclusions: Results indicated that ACL reconstruction was followed by a progressive increase in stability and a progressive decrease in variability over the postoperative rehabilitation period. In terms of stability and gait variability, six months of physiotherapy for rehabilitation after ACL reconstruction appears to be effective, but it is insufficient for a complete recovery as compared to healthy individuals.